Betty Bunny loves chocolate cake - Kaplan, Michael B. (Dial Books for Young Readers, 2011)
From her first bite, young Betty Bunny likes chocolate cake so much that she claims she will marry it one day, and she has trouble learning to wait patiently until she can have her next taste.